(3GdOQQ GdaQGFO aj TQM cJGH GdbhGYO aj Gdabg ddYdGeI GdMdis - (3eMeO MSf GdeXaQs; (3GHf GdeWgQ GdMdj , LeGd GdOjf , CHh efUhQ,J (B726 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd eMeO GdMSf Hf Gdabjg GdGcHQ eMeO Hf YHOGddg GdeXaQ, s
(3BNQgG (B:s
(3Ef TFJ GSJCfaJ Ydi GdKGfjI gh GdESJFfGa YdjgG HYO GdaQGZ ef GdUdGI Ydi GdChdi s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3Hg fXGe GdJYbjHIs
(3LRA BNQ s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3abg GdePGgH GdCNQis